Considerations of mineralogy and permeability testing of selected Sand/Bentonite mixes - Makgekgenene, Boné (Department of Civil Engineering, 2023)
The disposal of municipal, commercial and industrial waste contained in near impervious lining systems still poses challenges in terms of sustainability and long-term durability. This thesis assesses the engineering behaviour and chemical performance of selected Sand/Bentonite mixes to be used in the context of an environmentally inert landfill liner. Numerous test series in the laboratory focused on the permeability as a consequence of the physio-chemical characteristics of the selected mixes of two South African Bentonites and locally available sands. Several exploratory techniques (i.e., Cation Exchange Capacity; X-Ray Fluorescence; Scanning and Transmission Electron Microscopy) were employed to obtain the respective properties of the test materials. A flexible membrane test setup in connection with the falling head principle was used to determine the permeability of the mixes. A wide variety of bentonite percentage mixes (by mass) and a range of confinement pressures were investigated. The testing schedule catered for high and low compaction energy levels, hence covering a wide range of densities of the barrier material. The results of the exploratory techniques reveal valuable information on the quality and uniqueness of the two types of bentonites and allow comparative studies of their performance within a technical application. In the context of permeability, the grain size distribution, all round pressure, compaction, hydraulic gradient, quantity and distribution of bentonite within a mix contribute immensely towards the coefficient of permeability of any sand/bentonite mix. A visual presentation of the interrelationship of bentonite content, density of the mixes, confinement and coefficient of permeability is presented.